THE IMPORTANCE OF GAMES IN TEACHING ENGLISH (Ustozlar uchun, 2025)
The integration of games in teaching English has proven to be an effective and engaging strategy for enhancing language acquisition. Games provide a dynamic and interactive learning environment, fostering creativity, motivation, and active participation among students. By incorporating elements of competition, collaboration, and entertainment, games cater to diverse learning styles and reduce language anxiety, thereby encouraging communication in English. They also offer opportunities to practice vocabulary, grammar, pronunciation, and conversational skills in real-world contexts. This article explores the pedagogical benefits of using games in English language teaching, examines various gamebased methods, and highlights their role in developing critical language skills. The findings emphasize the importance of blending traditional teaching methods with innovative gamebased approaches to create a holistic and enjoyable learning experience.